The Influence of Digital Marketing and Service Quality on Consumer Interest in Using the Services of BTSA Logistics Medan: Pengaruh Digital Marketing dan Kualitas Pelayanan terhadap Minat Konsumen Menggunakan Jasa BTSA Logistics Medan - Shenny Angelina; Afrizal; Melissa Mangali; Rabel Catayoc (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
A successful marketing plan is essential for piquing customer interest in buying items, pushing businesses to become more competitive with both local and international rivals. BTSA Logistics, an Indonesian shipping firm, began operations in Medan in 2000. According to data on the quantity of containers and revenue, BTSA Logistics Medan has fallen short of its goals. It is believed that this is due to two key reasons: poor service quality and a digital marketing plan that is still underdeveloped. This study included all 608 clients who completed transactions with BTSA Logistics Medan in 2024. The Slovin formula was used to calculate the study's sample size, which was 241 respondents. The study's findings suggest that digital marketing has a limited impact on interest in utilizing BTSA Logistics Medan's services. Service quality has a partial impact on interest in utilizing BTSA Logistics Medan services. Digital marketing and service quality have a combined impact on interest in utilizing BTSA Logistics Medan services.